Implementation outcomes of national decentralization of integrated outpatient services for severe non‐communicable diseases to district hospitals in Rwanda. Issue 8 (16th May 2021) - Niyonsenga, Simon Pierre; Park, Paul H.; Ngoga, Gedeon; Ntaganda, Evariste; Kateera, Fredrick; Gupta, Neil; Rwagasore, Edson; Rwunganira, Samuel; Munyarugo, Antoine; Mutumbira, Cadet; Dusabayezu, Symaque; Eagan, Arielle; et al.
Abstract: Objectives: Effective coverage of non‐communicable disease (NCD) care in sub‐Saharan Africa remains low, with the majority of services still largely restricted to central referral centres. Between 2015 and 2017, the Rwandan Ministry of Health implemented a strategy to decentralise outpatient care for severe chronic NCDs, including type 1 diabetes, heart failure and severe hypertension, to rural first‐level hospitals. This study describes the facility‐level implementation outcomes of this strategy. Methods: In 2014, the Ministry of Health trained two nurses in each of the country's 42 first‐level hospitals to implement and deliver nurse‐led, integrated, outpatient NCD clinics, which focused on severe NCDs. Post‐intervention evaluation occurred via repeated cross‐sectional surveys, informal interviews and routinely collected clinical data over two rounds of visits in 2015 and 2017. Implementation outcomes included fidelity, feasibility and penetration. Results: By 2017, all NCD clinics were staffed by at least one NCD‐trained nurse. Among the approximately 27 000 nationally enrolled patients, hypertension was the most common diagnosis (70%), followed by type 2 diabetes (19%), chronic respiratory disease (5%), type 1 diabetes (4%) and heart failure (2%). With the exception of warfarin and beta‐blockers, national essential medicines were available at more than 70% of facilities. Clinicians adhered to clinical protocols at approximately 70% agreement with evaluators. Conclusion: The government of Rwanda was able to scale a nurse‐led outpatient NCD programme to all first‐level hospitals with good fidelity, feasibility and penetration as to expand access to care for severe NCDs.